Kepemimpinan Islami Aparat Desa Pengaruhnya terhadap Kepuasan Masyarakat: - Dwiarni, Aldavia Hesti; Yasin, Ach. (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
The purpose of this study was to understand the influence of the Islamic leadership style of village officials on community satisfaction at the Leranwetan Village Office. This research was conducted with an associative quantitative approach. This research was conducted at the Leranwetan Village Office with a total of 100 respondents, but the population surveyed was residents of Leranwetan Village. This research uses incidental sampling with non-probability sampling technique. Data collection was carried out using the questionnaire or questionnaire method which was distributed directly via the Google form and then evaluated using a Likert scale and the SMARTPLS program version 4.0 with the SEM analysis method. The results of this study indicate that when viewed partially the Islamic leadership variable (X) has a positive and significant effect on community satisfaction variable (Y). Keywords: Islamic Leadership, Community Satisfaction